Negative and positive politeness strategies in the syntactic structures and hedging devices used in conversation in Bua Fiji Hindi - Romina Singh; Kenel Keneshwar Singh; Sakul Kundra (Cogent Arts & Humanities)
This paper investigates the negative and positive politeness strategies used in the syntactic structures and hedging devices in conversation in Bua Fiji Hindi. Studies on politeness in different cultures have received the attention of anthropologists and linguists. This research was based on Brown and Levinson’s, Grice’s and Lakoff’s models of politeness strategies. This work is innovative since politeness has not been studied in Fiji Hindi, and is based on recorded natural discourse. Thirty discussions were recorded and translated. The information was coded into several sentence-level classes and, after that examined. In this paper, analysis of six types of hedging devices in the conversation will be presented – subjectivity markers, performative hedges, clausal mitigators, downgraders, proverbs and politeness maxims. Together with this, syntactic strategies such as honorificity in pronominal use, plurality in verbs, use of particles, and syntactic structures in requests will also be presented. The most significant difference found in the analyses is that females tend to use subjectivity markers predominantly. The research however, did not reveal any gender differences in using syntactic strategies. This research may inspire some new ideas concerning politeness strategies across different cultures in order to understand how cultural differences play a role in people’s politeness behaviour in conversations.